A 3-CS Distributed Federated Transfer Learning Framework for Intelligent Edge Optical Networks - Yang, Hui; Yao, Qiuyan; Bao, Bowen; Li, Chao; Wang, Danshi; Zhang, Jie; Cheriet, Mohamed (Frontiers in Communications and Networks, 2021)
With the rapid development of optical network and edge computing, the operation efficiency in edge optical network becomes more and more important, requiring an intelligent approach to enhance the performance of network. To realize an intelligent edge optical network, this paper firstly provided the demand under the development of edge optical network, and then presented a cross-scene, cross-spectrum, and cross-service (3-CS) architecture for edge optical networks, and finally proposed a federated transfer learning (FTL) framework, realizing a distributed intelligence edge optical network. The usability of the proposed framework is verified by simulation.